A NOTE ON CONTINUED FRACTIONS AND 3ψ3 SERIES - Pathak, Maheshwar; Srivastava, Pankaj (Italian Journal of Pure and Applied Mathematics, 2010)
The present paper concerns with the continued fraction representation for 3ψ3 basic bilateral hypergeometric series. Several special cases are also discussed.